The standardization of biodiversity: how politicization changes standardization for corporate sustainability reporting - Zenglein, Florian (Frontiers in Sustainability, 2025)
This article asks how politicization changes the standardization of biodiversity in the realm of corporate sustainable reporting (CSR) frameworks. The study encompasses three areas: First, the participatory processes in standardization; second, the substantive prioritization of conservation considerations over economic aspects within standards; and third, the interplay between private and public standard-setting bodies. It argues that the European Union (EU) is taking on a more assertive role, shaping corporate reporting practices and the standards established by private organizations. Additionally, the standard-setting process is evolving from a technical exercise to a more politicized undertaking. The introduction of the EU Green Deal (EUG) brought in new biodiversity regulations, CSR frameworks, and standards, resulting in a new dynamic in politicizing biodiversity standardization. As a result, the number of actors with opposing interests is increasing, thereby intensifying the contestation of the standardization of biodiversity. Therefore, political rather than technical considerations increasingly drive biodiversity standardization processes in the EU. The EU is progressively expanding its role in two distinct yet complementary ways. Firstly, it is implementing political objectives through targeted reporting. Secondly, it provides an arena in which various actors are included. To elaborate on this argument, a qualitative analysis in the European context is conducted, highlighting the dynamics in the development of standards in CSR frameworks. Accordingly, the analysis encompasses standards and frameworks proposed by the EU, as well as by private standard-setting bodies GRI, ISO, ISBB, and CDP.